Immune modulation of Th1/Th2/Treg/Th17/Th9/Th21 cells in rabbits infected with Eimeria stiedai - Chen, Xiao-Di; Xie, Jing; Wei, Yong; Yu, Ji-Feng; Cao, Ye; Xiao, Lu; Wu, Xue-Jing; Mao, Cong-Jian; Kang, Run-Min; Ye, Yong-Gang (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Despite long-term integrated control programs for Eimeria stiedai infection in China, hepatic coccidiosis in rabbits persists. Th1, Th2, Th17, Treg, Th9, and Th21 cells are involved in immune responses during pathogen infection. It is unclear whether Th cell subsets are also involved in E. stiedai infection. Their roles in the immunopathology of this infection remain unknown. Therefore, monitoring these T-cell subsets’ immune responses during primary infection of E. stiedai at both transcriptional (mRNA) and protein (cytokines) levels is essential. Methods In experimentally infected New Zealand white rabbits, mRNA expression levels of their transcript—TBX2 (Th1), GATA3 (Th2), RORC (Th17), Foxp3 (Treg), SPI1 (Th9), and BCL6 (Th21)—were evaluated using quantitative real-time polymerase chain reaction (qRT-PCR), whereas Th1 (IFN-g and TNF-a), Th2 (IL4), Th17 (IL17A and IL6), Treg (IL10 and TGF-b1), Th9 (IL9), and Th21 (IL21) cytokines were measured using enzyme-linked immunosorbent assays (ELISAs). Results We found that levels of TBX2, GATA3, RORC, SPI1, and BCL6 in the livers of infected rabbits were elevated on days 5 and 15 post-infection (PI). The concentrations of their distinctive cytokines IFN-g and TNF-a for Th1, IL4 for Th2, IL17A for Th17, IL9 for Th9, IL21 for Th21, and IL10 for Treg IL10 were also significantly increased on days 5 and 15 PI, respectively (p < 0.05). On day 23 PI, GATA3 with its cytokine IL4, RORC with IL17A, Foxp3 with IL10 and TGF-b1, and SPI1 with IL9 were significantly decreased, but TBX2 with IFN-g and IL6 remained elevated. Discussion Our findings are the first evidence of Th1/Th2/Treg/Th17/Th9/Th21 changes in E. stiedai-infected rabbits and provide insights into immune regulation mechanisms and possible vaccine development.